Climate change biology - Hannah, Lee Jay (Academic Press, 2011)
Climate change biology is a new discipline, born of the recognition that human-induced climate change is resulting in wholesale shifts in the distributions of species and the timing of biological events. The evidence for biological upheaval in response to climate change is immense. Migratory species are arriving earlier in the year. Flowers are blooming earlier. Ranges of plants, mammals and insects are moving. Food chains are being disrupted. And, unfortunately, the first extinctions linked to climate change are already being recorded in the dozens. Climate change biology is not only abo.